Generalized Anxiety Disorder and Sleep Quality of Day Laborers during COVID-19 Pandemic (Medicine Today, 2025)
Introduction: Since December 2019, Coronavirus Disease (COVID-19) has had a significant impact on the world. It had severe economic repercussions in Bangladesh. The lockdown had interfered with the production, availability, and supply of enough food. As a result, food prices have increased, making it harder for low-income individuals, such as day laborers, to survive. Aims and objectives: The purpose of the study was to determine the level of generalized anxiety disorder (GAD) and evaluate the association between sleep quality and GAD among day laborers during the COVID-19 pandemic. Materials and Methods: This cross-sectional study was conducted among 227 construction workers, rickshaw pullers, van pullers, and other day laborers from the Faridpur district. Participants were conveniently selected and interviewed in person using a semi-structured questionnaire, with data collection taking place at their convenience from January to December 2020. Results: The majority of respondents reported minimal anxiety (75.3%), followed by mild anxiety (14.5%), moderate anxiety (9.7%), and severe anxiety (0.4%). most respondents had good sleep quality (74.4%), while 25.6% experienced poor sleep quality. A strong positive correlation was observed between GAD scores and sleep quality scores (p